Regulating Migrant Integration in Europe : The Case of Skills - McCormack-George, Dáire, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
Migrants coming to and moving within Europe typically experience inadequate recognition of their professional qualifications and wrongful discrimination. This book describes and critically assesses international, European and EU laws and policies governing migrant integration in Europe, with a particular focus on those concerning the recognition of migrants' skills. It argues that at least certain parts of EU law require clarification, restatement and even reform. The book formulates practical proposals to improve the governance of migrant integration in Europe, making it more coherent, effective and fair.